Road traffic accidents among commercial motorcyclists: Relationship with substance use and psychosocial factors - Adetunji Obadeji; Banji Ferdinand Kumolalo; Janet Olufisayo Bamidele; Tolulope Funmilayo Olasehinde (Wolters Kluwer Medknow Publications, 2020)
Introduction: Road traffic accidents (RTAs) constitute a major source of death, morbidity, and disability, with a disproportionate number occurring in developing nations. This study was aimed at evaluating the rate of RTA among commercial motorcyclists and identified psycho-social as well as substance use variables associated with it. Methods: This was a cross-sectional study among commercial motorcyclists in Ado-Ekiti, Nigeria. Participants were assessed with sociodemographic questionnaire, the condensed Alcohol, Smoking and Substance Involvement Screening Test and Patient Health Questionnaire, the 9-item version. Chi-square tests and the odds of developing RTA were calculated for current substance use variables and other variables of interest. Results: Two hundred and thirty-four (51.3%) reported to have experienced one form of accident or the other, of which majority reported major injuries that necessitated hospital in-patient care and 3.0% had fatality. No significant association between history of RTA and sociodemographic characteristics (P > 0.05). Participants with a history of current marijuana use (odds ratio [OR] = 1.77 [95% confidence interval (CI) = 0.89-3.51]) tobacco use (OR = 1.45 [95% CI = 0.90-2.34]), alcohol use (OR = 1.49 [95% CI = 1.02-2.17]), and depression (OR = 1.50 [95%CI = 0.97-2.33]) had a higher risk of experiencing RTA compared to those without such history. Significantly, those with a history of current use any substance (OR = 1.55 [95% CI = 1.07-2.24]) (P = 0.04) and alcohol (OR = 1.49 [95% CI = 1.02-2.17]) (P = 0.02) were more likely to have had RTA compared to those without history of current use of any substance. Conclusion: There is a high rate of RTA among motorcyclists studied, with most reporting a major accident that required some form of hospital care, thus increasing the burden on the already over-burdened health systems. Among other factors, effort at reducing RTA among motorcyclists should also focus on reducing substance use.